PERSEPSI MASYARAKAT TERHADAP TAYANGAN IKLAN ROKOK PADA MEDIA INTERNET - Yurita Amarya; Ratna Widyayanti; Jamilah Nasution (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Problems related to cigarette smoking cause controversy in Indonesia, including cigarette advertising on the internet. There are currently many cigarette advertisements on the internet that air almost all the time and can be accessed by teenagers and children. The phenomenon of the younger age who have started smoking and the increasing number of novice smokers is certainly worrying. Incessant cigarette advertising including advertisements on the internet can make cigarettes a daily necessity. This study aims to determine the public's response to the influence of cigarette advertising on the internet and how to support the community if a ban on cigarette advertising is imposed on the internet. The method used is the descriptive method by collecting quantitative data using a questionnaire to determine respondents' perceptions and attitudes towards cigarette advertisements on the internet and the prohibition of cigarette advertisements on the internet. The results showed that 98% of respondents opinions that cigarette advertising did not affect a person's desire to consume cigarettes. In addition, as many as 55% of respondents strongly agree that cigarette advertising is removed from the internet, and 45% of respondents stated that if cigarette advertising is stopped it can help them to stop smoking. Based on the results of this study, it can be concluded that cigarette advertising does not affect a person to consume cigarettes and that the community strongly supports/agrees if the prohibition on cigarette advertising is enforced on the internet and would help to stop smoking.